An experimental investigation on how proper interior task lighting systems solve residential kitchen ergonomic problems in a Filipino upper middle class setting - Chan, Maria Lourdes Balmaceda (1998.)
(no abstract provided by the author)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Kitchens -- Philippines; Interior decoration